1996
DOI: 10.1002/cvde.19960020612
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature deposition of AIN films by an alternate supply of trimethyl aluminum and ammonia

Abstract: AlN thin films were grown by an alternate supply of trimethyl aluminum (TMA) and ammonia, i.e., according to the processing scheme of the atomic layer epitaxy (ALE) technique. In contrast with the ideal ALE process, no saturation of the growth rate was observed with increasing TMA pulse time. In addition, with fixed pulse times the growth rate was strongly temperature dependent. These observations were interpreted in terms of a self-decomposition of "MA. Despite the absence of selflimitation, the films were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 36 publications
3
70
1
Order By: Relevance
“…Growth rate per cycle (GPC) data suggests that below 200 C, the GPC remains almost constant at 0.84 Å where the growth mechanism is controlled by selflimited surface reactions, i.e., incoming precursor molecules can only react with the species bound on the surface and gasphase reactions are eliminated. 5 TMA and NH 3 saturation was observed at 185 C in the "self-limiting ALD window" where the GPC is independent of the growth temperature and precursor dose. Furthermore, in our experiments the saturation of TMA was achieved at much shorter pulse times whereas longer metallic precursor pulse times were used in other ALD-grown AlN experiments.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Growth rate per cycle (GPC) data suggests that below 200 C, the GPC remains almost constant at 0.84 Å where the growth mechanism is controlled by selflimited surface reactions, i.e., incoming precursor molecules can only react with the species bound on the surface and gasphase reactions are eliminated. 5 TMA and NH 3 saturation was observed at 185 C in the "self-limiting ALD window" where the GPC is independent of the growth temperature and precursor dose. Furthermore, in our experiments the saturation of TMA was achieved at much shorter pulse times whereas longer metallic precursor pulse times were used in other ALD-grown AlN experiments.…”
Section: Resultsmentioning
confidence: 97%
“…While high-temperature (typically above 1100 C) grown epitaxial AlN films are widely used in active electronic and optoelectronic device layers, polycrystalline and amorphous AlN films grown at CMOS-compatible temperatures (lower than 300 C) find potential use as dielectric passivation layers for microelectronic devices. 5 Atomic layer deposition (ALD) is a distinguished and alternative chemical vapor deposition technique to prepare conformal thin film coatings at low temperatures (typically below 300 C). 1 The most important feature of an ALD process is the selflimiting growth behavior due to the self-limiting surface reactions occurring for both precursors in each half-cycle.…”
Section: Introductionmentioning
confidence: 99%
“…AlN growth by ALD has been studied by several research groups [23][24][25][26][27][28][29]. Lee et al [23] reported plasma-enhanced ALD (PEALD) of AlN at 350°C using aluminum chloride (AlCl 3 ) and NH 3 /H 2 plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Growth rate of this process saturated at~0.42 Å/cycle, resulting with films composed of microcrystallites of wurtzite (100) in an amorphous AlN matrix [24]. Thermal [25,26], plasma-enhanced [26], and UV-assisted [27] ALD of AlN using trimethylaluminum (TMA) and ammonia (NH 3 ) have been studied within the temperature ranges of 320-470, 250-470, and 240-370°C, respectively -however, no self-limiting growth behavior was observed. This was explained by Riihela et al [25] by the fact that surface reactions between TMA and NH 3 occur with reasonable rates only at temperatures where TMA self-decomposition takes place.…”
Section: Introductionmentioning
confidence: 99%
“…ALD of AlN thin films has been studied by several research groups (3)(4)(5)(6)(7)(8)(9). Lee et al (3) reported plasma-enhanced ALD (PEALD) of AlN at 350 °C using aluminum chloride (AlCl 3 ) and NH 3 /H 2 plasma.…”
Section: Introductionmentioning
confidence: 99%